Combined training improves the diagnostic measures of sarcopenia and decreases the inflammation in HIV‐infected individuals. Issue 2 (9th February 2022) - Ghayomzadeh, Morteza; Hackett, Daniel; SeyedAlinaghi, SeyedAhmad; Gholami, Mohammad; Hosseini Rouzbahani, Negin; Azevedo Voltarelli, Fabrício
Abstract: Background: HIV‐related sarcopenia is an emerging health issue that often remains undiagnosed and can lead to reduced quality of life, independence, and premature death if untreated. This study investigated the effects of a 6 month combined training (resistance plus aerobic exercise) (CT) intervention on diagnostic measures of sarcopenia, including grip strength, appendicular lean mass index (ALMI), and gait speed. Methods: Forty participants were randomized into either a CT group ( n  = 20; age = 38.3 ± 4.9 years) or a control group (CON; n  = 20; age = 37.9 ± 5.1 years). Participants in the CT group performed three supervised sessions per week for 6 months, consisting of weekly reverse linear periodized resistance training followed by 20 min aerobic training. Participants in the CON group were instructed to continue with their current lifestyle habits. Assessments were completed at baseline and after 6 months. Statistical analyses were performed using a two‐way analysis of covariance (ANCOVA) adjusted for sex and preintervention values. Primary outcomes included grip strength, ALMI, and gait speed. Secondary outcomes were changes in levels of pro‐inflammatory cytokines (IL‐6 and TNF‐α), IGF‐1, and myostatin. Associations were explored between changes in inflammatory markers (IL‐6 and TNF‐α), gait speed, and ALMI with grip strength. Results: A significant increase in ALMI was found for CT compared with CON (0.29 ± 0.13 kg/m 2 vs. −0.11 ± 0.14 kg/m 2, respectively; P  < 0.001). Significant improvements in grip strength (7.86 ± 8.50 kg for CT vs. −1.58 ± 2.47 kg for CON) and gait speed (0.16 ± 0.07 m/s 2 for CT vs. −0.06 ± 0.52 m/s 2 for CON; both P  < 0.001) were also observed in CT compared with CON. Reduction in inflammatory biomarkers was found in CT compared with CON (IL‐6; TNF‐α, both P  < 0.001). An increase in IGF‐1 (74.36 ± 56.64 pg/mm 3 for CT vs. 7.19 ± 99 pg/mm 3 for CON; P  < 0.001) and a decrease in myostatin (−158.90 ± 62.03 pg/mm 3 for CT vs. −43.33 ± 146.60 pg/mm 3 for CON; P  < 0.001) was found following CT compared with the CON group. Change in grip strength was correlated with changes in IL‐6 ( r  = −0.65, P  < 0.001), TNF‐α ( r  = −0.63, P  < 0.001), gait speed ( r  = 0.63, P  < 0.001), and ALMI ( r  = 0.54, P  = 0.001), but not IGF‐1 and myostatin. No adverse events were recorded, and compliance with the CT exercise sessions was high (>85%). Conclusions: Combined training appears to be an effective means to counteract sarcopenia and improve various inflammatory markers and growth hormones in people living with HIV.